Forest bathing enhances sleep, mood, and immunity: insights from low-latitude evergreen broad-leaved forests - Xiangheng Dai; Dongteng Liao; Jianghua Ouyang; Hongwei Xiao; Zhongjie Tian; Liujin Qiu; Jinmei Yang; Hao Wang; Hao Wang; Daocheng Gong; Daocheng Gong; Zhaojia Li; et al. (Frontiers in Forests and Global Change, 2025)
IntroductionRapid urbanization and environmental degradation have escalated health challenges such as sleep disturbances, mood disorders, and chronic stress. Forest bathing, derived from Japan’s Shinrin-yoku, offers immersive sensory engagement with nature, providing psychological and physiological benefits. Low-latitude evergreen broad-leaved forests may amplify these benefits due to phytoncides and negative ions.MethodsIn this prospective cohort study, 36 healthy young participants recruited via WeChat were assessed within Tianjing Mountain Forest in Guangdong Province. Pre- and post-intervention evaluations used standardized measures: Athens Insomnia Scale (AIS), Self-Rating Scale of Sleep (SRSS), Profile of Mood States (POMS), and Perceived Stress Scale (PSS). Routine blood tests, lymphocyte subset profiling, and immune markers (Aquaporin 9 (AQP9), Heat Shock Protein A6 (HSPA6), salivary immunoglobulin A (IgA) (salivary IgA), and lysozyme) were measured immediately, one week, and one month post-intervention.ResultsSignificant improvements were observed across multiple domains. Sleep quality improved with decreased AIS scores during the intervention and lower SRSS scores up to one month post-intervention. POMS and PSS scores declined, indicating mood and stress improvements. Physiologically, transient hemoglobin and red blood cell increases occurred, with platelet normalization by one month. Immune profiling showed increased total, regulatory, and helper T cells, an improved CD4/CD8 ratio, and elevated B lymphocytes at one month. Serum AQP9 and HSPA6 levels decreased, while salivary IgA and lysozyme surged.DiscussionThese findings suggest forest bathing offers immediate and multidimensional health benefits, highlighting its potential as a non-pharmacological intervention for holistic well-being. The study advocates integrating natural spaces into urban planning and public health strategies to promote health in urbanized populations.Clinical trial registrationThis study had been registered at the China Clinical Trial Registration Center (registration number: ChiCTR2500096972; https://www.chictr.org.cn/showproj.html?proj=241942).